GENDER BASED VIOLENCE: THE RELATIONSHIP OF LAW AND PATRIARCHY IN INDONESIA - Muhammad Kholis Hamdy; M Hudri (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2022)
Abstract. This article briefly examines Gender Based Violence (GBV) in Indonesia based on the 2021 and 2022 reports of the National Commission on Violence Against Women/Komnas Perempuan (NCVAW). It seeks to understand (GBV) and violence against women (VAW) viewed as a product of patriarchy that socially constructs and defines gender roles, gender relations, and power relations. Among several arguments, VAW cases are due to the vulnerable position of women caused by patriarchy that discriminates and subordinates women, in addition to the unequal power relation between men and women, husbands and wives, children and parents, other family members, friends, and colleagues. One perspective is selected to understand this violence: policy or law, providing directions from which this study focuses. Patriarchy or varieties of patriarchy applied in this work provide a brief theoretical tool of analysis to scrutinize GBV in Indonesia by assessing regulations and reports. This study employs a qualitative research approach that focuses on scrutinizing regulations and 2021 and 2022 reports. The findings suggest that GBV in Indonesia relates to the defined prescription of the husband and wife relationship in the marriage regulations. Patriarchal values may have shaped unequal social arrangements, gender roles, gender relations, and understandings of power relations at the macro and micro levels. Approaches to studying law and regulations concerning GBV are varied and complex. Theorising patriarchy and varieties of patriarchy are still relevant. The limitation of this article is that it offers broad contexts. Therefore, articulate research based on specific perspectives and distinct theories on these reports remains widely interesting. Keywords: Gender Based Violence, Violence Against Women, Law, Patriarchy. Abstrak. Artikel ini meneliti secara singkat mengenai kekerasan berbasis gender (Gender Based Violence/GBV) di Indonesia berdasarkan laporan Komisi Nasional (Komnas) Perempuan. Tulisan ini berupaya memahami GBV dan kekerasan terhadap perempuan (Violence Against Woman/VAW) sebagai produk patriarki yang mengonstruksi dan mendefinisikan secara sosial mengenai peran gender, relasi gender, dan relasi kuasa. Di antara banyak penjelasan, kasus VAW disebakan oleh rentannya posisi perempuan akibat patriarki yang mendiskriminasi dan mensubordinasi perempuan, serta timpangnya relasi kuasa antara laki-laki dan perempuan, suami dan istri, anak-anak dan orang tua, anggota keluarga, teman, dan rekan kerja. Ada satu perspektif untuk memahami kekerasan: yakni kebijakan atau hukum, yang menyediakan arah di mana kajian ini mengambil fokus. Patriarki atau berbagai jenis dari patriarki yang digunakan di dalam penelitian ini menjadi alat analisis teoritis singkat untuk meninjau GBV di Indonesia dengan menilai aturan dan laporan. Kajian ini menggunakan pendekatan penelitian kualitatif yang berfokus pada peninjauan regulasi dan laporan tahun 2021 dan 2022. Hasil penelitian ini menjelaskan bahwa GBV di Indonesia berkaitan dengan aturan relasi suami istri yang ditetapkan di dalam pernikahan. Nilai-nilai patriarkis menciptakan ketimpangan di dalam tatanan sosial, peran dan relasi gender, serta pemahaman tentang relasi kuasa di tingkat makro dan mikro. Pendekatan terhadap kajian hukum dan peraturan yang berfokus pada GBV beragam dan kompleks. Namun teori patriarki dan jenis-jenis patriarki masih relevan. Pembatasan penelitian ini menawarkan konteks yang mendalam karena mengartikulasikan penelitian berdasarkan pada perspektif yang spesifik dan teori yang khas pada laporan ini tetaplah sangat menarik.Kata kunci: Kekerasan Berbasis Gender, Kekerasan terhadap Perempuan, Hukum, Patriarki.